Crack cravings in users undergoing treatment in psychosocial care centers - Lappann, Nadja Cristiane; Machado, Jacqueline Simone de Almeida; Tameirão, Felipe Viegas; Benjamim, Maria Luísa Nogueira (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2015)
The aim of this study is to evaluate cravings in crack users undergoing treatment in Psychosocial Care Centers. This was a descriptive cross-sectional study with a quantitative approach. The sample was made up of 20 crack users and data were collected using the Cocaine Craving Questionnaire-Brief. The profile identified was characterized as young single men with a low level of schooling. Higher scores for cravings were found in those who had been using crack for more than three years, and the shorter the period of abstinence from the drug, the greater the craving. Cravings are a significant variable in treating drug addicts, helping to prevent relapse.